2022
DOI: 10.1186/s13065-022-00795-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in silico molecular docking analysis, pharmacokinetic properties and evaluation of antibacterial and antioxidant activities of fluoroquinolines

Abstract: Background Quinolines have demonstrated various biological activities such as antimalarial, antibacterial and anticancer. Hence, compounds with such scaffold have been used as lead in drug development. This project is, therefore, aimed to synthesis and evaluates some biological activities of quinoline analogs. Methods 2-Chloro-7-fluoroquinoline-3-carbaldehydes were synthesized by the application of Vilsmeier–Haack reaction. The chlorine in the fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Only L 2 and MnL2 can have AMES Toxicity. All other results of the toxicity predictions (Table 9) showed that these compounds are less toxic [37].…”
Section: Physicochemical Parameters Generated Using Swissadme Toolmentioning
confidence: 80%
See 1 more Smart Citation
“…Only L 2 and MnL2 can have AMES Toxicity. All other results of the toxicity predictions (Table 9) showed that these compounds are less toxic [37].…”
Section: Physicochemical Parameters Generated Using Swissadme Toolmentioning
confidence: 80%
“…Interaction of molecules with cytochrome P450 (CYP) enzymes is essential because these isoenzymes may result in unwanted adverse side effects by lowering the solubility and the accumulation of the drug or its metabolites. Predictions revealed that STZ exhibits non-inhibitor for all the enzymes, L1 inhibits only CPY1A2, CYP2C9, and CYP3A4, L2 inhibits CYP2C19, CYP2C9, CYP2D6, and CYP2D6, MnL1 inhibit only CYP2C9, ciprofloxacin act as non-inhibitor whereas fluconazole inhibits CYP2C19 [37]. Druglikeness is a prediction that determines whether a particular pharmacological agent has properties consistent with being an orally active drug or not, in which this prediction is based on the Lipinski rule of five, Ghose filter, Veber's rule, Egan, Muegge and Bioavailability score.…”
Section: Physicochemical Parameters Generated Using Swissadme Toolmentioning
confidence: 99%
“…Geronikaki et al [ 39 ] used SwissADME to examine the drugability of various bioactive compounds in their study. Fekadu et al [ 40 ] also acknowledged the significance of SwissADME as an in silico tool by using it to assess the drug-like properties of different compounds in their study. Even with all the 16 molecules satisfying the requirements of the SwissADME drug-likeness filters, their success as drug candidates against COVID 19 depended on their binding affinities to SARS-CoV-2 M pro as well; hence, they were docked to the viral main protease using Pyrx software.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking studies were also carried out to verify and rationalize anti-bacterial properties of some synthesized compounds with promising MIC and MBC values indicating on possible structural modification for achieving better anti-bacterial activity. Some examples include molecular docking studies of synthesized pterostilbene derivatives against DNA polymerase ( Tang et al., 2019 ), fluoroquinolones derivatives against E. coli DNA gyrase B ( Fekadu et al., 2022 ), quinoline derivatives against S. aureus tyrosyl-tRNA synthetase ( Bouzian et al., 2020 ), diclofenac derivatives against DNA gyrase ( Hamed et al., 2023 ).…”
Section: In Silico Methods For Evaluation Of Novel Compoundsmentioning
confidence: 99%